Misrepresenting COVID-19: Lying With Charts During the Second Golden Age of Data Design. (January 2021) - Doan, Sara
In this second golden age of data design, digital affordances enable the news media to share occasionally misleading charts about COVID-19. Examining data visualizations about COVID-19 highlights three ways that charts can mislead viewers: (a) by displaying inadequate data, (b) by manipulating scales and visual distance, and (c) by omitting contextual labels needed to fully understand a chart's message. This article provides takeaways for technical communicators about including and displaying adequate data, representing numbers consistently, and humanizing COVID-19's effects.